2015
DOI: 10.1007/s10661-015-4922-7
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing nonlinear variations in terrestrial vegetation in China during 1982–2012

Abstract: Quantifying the long-term trends of changes in terrestrial vegetation on a large scale is an effective method for detecting the effects of global environmental change. In view of the trend towards overall restoration and local degradation of terrestrial vegetation in China, it is necessary to pay attention to the spatial processes of vegetative restoration or degradation, as well as to clarify the temporal and spatial characteristics of vegetative growth in greater geographical detail. However, traditional lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…These results agree with those obtained by Yang et al [65]. This change rate is larger than the change rate in China (0.007/10 a from 1982 to 2011) [66,67], and it is also larger than the Loess Plateau (0.025/10 a, from 1982 to 2013) [66] and Tibetan Plateau (0.004/10 a from 1982 to 2012) [68]. The slope is the change rate of vegetation growth, and P represents the significance degree.…”
Section: Interannual Variations In Ndvisupporting
confidence: 93%
“…These results agree with those obtained by Yang et al [65]. This change rate is larger than the change rate in China (0.007/10 a from 1982 to 2011) [66,67], and it is also larger than the Loess Plateau (0.025/10 a, from 1982 to 2013) [66] and Tibetan Plateau (0.004/10 a from 1982 to 2012) [68]. The slope is the change rate of vegetation growth, and P represents the significance degree.…”
Section: Interannual Variations In Ndvisupporting
confidence: 93%
“…Our study showed that the region joining Shaanxi, Gansu, and Ningxia on the Loess Plateau experienced a decrease to increase trend of NPP, while the high mountains in Xinjiang exhibited an increase to decrease trend (Figure 2c), which are inconsistent with the monotonic increase trend claimed by Wu, Yu, Zhang, Du, and Zhang (2018). The trend reversal from decrease to increase in the region joining Shaanxi, Gansu, and Ningxia on the Loess Plateau was predominantly attributed to land development and ecological protection efforts (Liu et al, 2015). The extensive cultivation and the rapid development of husbandry industries caused vegetation degradation during the early years of the study period, whereas the implementation of the Grain to Green Program promoted vegetation growth and led to the trend reversal from decrease to increase (Xue et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The statistical results reveal that the average trends over Loess Plateau during S, S1, and S2 were 0.022/10a, 0.013/10a, and 0.059/10a, respectively. After 2000, the growth rate of vegetation over Loess Plateau was 4.5 times that before 2000, In addition, [35] shows that the vegetation change rate of the whole China during 1982-2012 is 0.002/10a, and the vegetation growth rate of Loess Plateau during S and S2 is 11 and 29.5 times than that of the whole China. From the spatial distribution of NDVI, vegetation decreased in the southern and northern portions of Loess Plateau, especially in area I.…”
Section: Vegetation Distribution Over the Loess Plateaumentioning
confidence: 88%